Self-supervised Lidar place recognition in overhead imagery using unpaired data - Tang, TY; De Martini, D; Newman, PM (Robotics: Science and Systems Foundation, 2023)
As much as place recognition is crucial for navigation, mapping and collecting training ground truth, namely sensor data pairs across different locations, are costly and time-consuming. This paper tackles these by learning lidar place recognition on public overhead imagery and in a self-supervised fashion, with no need for paired lidar and overhead imagery data. We learn the cross-modal data comparison between lidar and overhead imagery with a multi-step framework. First, images are transformed into synthetic lidar data and a latent projection is learned. Next, we discover pseudo pairs of lidar and satellite data from unpaired and asynchronous sequences, and use them for training a final embedding space projection in a cross-modality place recognition framework. We train and test our approach on real data from various environments and show performances approaching a supervised method using paired data.